Monitoring System for a Street Lighting Luminaire - Ramírez Murillo, Harryson; Arias Galvis, Iván Alberto; Garzón Huertas, Alfonso Germán (TECCIENCIA, 2020)
This research work shows a monitoring system for a public lighting luminaire. This system allows reducing time response under different kind of faults, such as short circuits in one of luminaries’ components. On the other hand, this development could contribute to improve the roads, pedestrian and vehicles safety. The proposed prototype has two microcontrollers which were used for transmitting (TX) and receiving (RX) devices, respectively. Likewise, it requires a luxes (lx) and current (A) sensors, real-time module, external memory and GSM devices. The Technical Regulation of Lighting and Street Lighting (RETILAP) states that is possible making a preventive maintenance when the luminaire efficiency is below than the 70%, which corresponds to 0.7 A current. Nowadays, is very important saving energy and using properly the environmental resources, due to the increasing of global warming effect.